การพัฒนาระบบบริหารสู่ความเป็นเลิศของโรงเรียนเอกชน สอนศาสนาอิสลามควบคู่วิชาสามัญ - บุญชม มนัส; อุสาโห ชญาพิมพ์ (Journal of Education Studies, Chulalongkorn University, 2014)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาสภาพปัจจุบันและสภาพที่พึงประสงค์ของระบบบริหาร โรงเรียนเอกชนสอนศาสนาอิสลามควบคู่สามัญตามเกณฑ์เพื่อการดำเนินการที่เป็นเลิศด้านการศึกษา ของ Malcolm Baldrige และเพื่อพัฒนาระบบบริหารสู่ความเป็นเลิศของโรงเรียนเอกชนสอนศาสนา อิสลามควบคู่วิชาสามัญ โดยใช้เกณฑ์คุณภาพการศึกษาเพื่อการดำเนินการที่เป็นเลิศของ Malcolm Baldrige เป็นฐาน วิจัยแบบผสมผสาน กลุ่มตัวอย่าง ๑๖๐ โรงเรียน เครื่องมือ คือ แบบสอบถาม และ การประชุมสนทนากลุ่ม วิเคราะห์ข้อมูลด้วยสถิติบรรยายและเทคนิค PNI Modif ied ผลการวิจัยพบว่า ๑) สภาพปัจจุบันด้านที่มีค่าเฉลี่ยมากที่สุดเท่ากับ ๓.๗๔ คือ ด้านการนำองค์การ สภาพที่พึงประสงค์ด้าน ที่มีค่าเฉลี่ยมากที่สุดเท่ากับ ๔.๓๒ คือ ด้านการนำองค์การ โรงเรียนกลุ่มภาคใต้ ด้านที่มีค่าเฉลี่ยของความ ต้องการจำเป็นสูงสุดเท่ากับ ๐.๒๕ คือ ด้านการวัดผลการวิเคราะห์ และการจัดการความรู้ โรงเรียนกลุ่ม ภาคกลาง ด้านที่มีค่าเฉลี่ยของความต้องการจำเป็นสูงสุด เท่ากับ ๐.๒๕ คือ ด้านการมุ่งเน้นผู้ปฏิบัติงาน ๒) ระบบบริหารสู่ความเป็นเลิศของโรงเรียนเอกชนสอนศาสนาอิสลามควบคู่วิชาสามัญที่พัฒนาขึ้น มี ๒ ระบบคือ (๑) ระบบบริหารโรงเรียนในภาคใต้ คือ ระบบบริหารสู่ความเป็นเลิศของโรงเรียนเอกชน สอนศาสนาอิสลามควบคู่วิชาสามัญมุ่งเน้นการวัดผล การวิเคราะห์ การจัดการความรู้และการปฏิบัติงาน (๒) ระบบบริหารโรงเรียนในภาคกลาง คือ ระบบบริหารสู่ความเป็นเลิศของโรงเรียนเอกชนสอนศาสนา อิสลามควบคู่วิชาสามัญ มุ่งเน้นผู้ปฏิบัติงานและการวัดผล การวิเคราะห์ การจัดการความรู้ This research focuses on studying the current situation and desirable situation of a management system toward excellence of private schools simultaneously teaching Islamic and general education based on the Malcolm Baldrige criteria for performance excellence, and to develop a management system toward excellence of private schools simultaneously teaching Islamic and general education. Mix method research was employed. The samples were taken from 160 schools. Instruments included questionnaires, interview forms and focus groups. The analysis used descriptive statistics and the technique called Modif ied Priority Needs Index was applied. The research found:1) The current situation is found to be the highest average = 3.74 is Leadership. The desirable situation is found to be the highest average = 4.32 is Leadership. The schools in the southern provinces indicated the maximum index of needs (PNIModif ied=0.24) were Measurement, Analysis, and Knowledge Management. The schools in the central region indicated the, maximum index of needs (PNIModif ied0.25) is Workforce Focus. 2) The management system toward excellence of private schools simultaneously teaching Islamic and general education is developed by two systems (1) Management system for the schools of Southern Thailand was a management system toward the excellence of private schools simultaneously teaching Islamic and general education based focus on Measurement was Analysis and Knowledge Management and Operations Focus. (2) The management system for the schools of the central region was the Management system toward excellence of private Islamic school toward excellence of private Islamic schools with general education subjects based on Operations Focus and focus on Measurement was Analysis and Knowledge Management.